Enhanced optical and electrical properties of zinc: SnO2 nanoparticles for optoelectronic applications. (2022) - Garg, Vijay; Kumari, Renu; Sharma, Harsh; Rehani, Divya; Kumar, Vipin; Saxena, Manish
Abstract: Tin oxide is an impressive metal oxide for optoelectronic applications and its properties can be easily augmented with doping. In current research work, undoped and zinc-doped SnO2 nanoparticles annealed at 500 °C were prepared by a solid-state reaction method. The rutile tetragonal structure for undoped and zinc-doped SnO2 nanoparticles was proved by the analysis of their x-ray diffraction (XRD) patterns. Scanning electron microscope (SEM) images confirm the spherical, smooth, and dense morphology. The presence of Sn, O, and Zn ions are supported by energy dispersive x-ray study (EDX). The transmission spectrum obtained by UV–Visible spectroscopy shows a blue shift and the energy band gap (Eg ) for undoped and zinc-doped SnO2 nanoparticles changes from 3.03 to 3.18 eV. Photoluminiscence (PL) spectra of synthesized samples shows one emission peak at 430 nm whose intensity increases with zinc-doping. The electrical resistivity was studied by Hall-effect measurement and it revealed that the resistivity decreases with zinc doping.